Answer:
If solving for y: y = 8 - 2x
If solving for x: x = [tex]\frac{8 - y}{2}[/tex]
Step-by-step explanation:
To solve for y:
Factor out the common term, which in this case is 3.
3(2x + y) = 24
Divide both sides by 3.
2x + y = [tex]\frac{24}{3}[/tex]
Simplify [tex]\frac{24}{3}[/tex] to 8.
2x + y = 8
Subtract 2x from both sides.
y = 8 - 2x
To solve for x:
Factor out the common term, which in this case is 3.
3(2x + y) = 24
Divide both sides by 3.
2x + y = [tex]\frac{24}{3}[/tex]
Simplify [tex]\frac{24}{3}[/tex] to 8.
2x + y = 8
Subtract y from both sides.
2x = 8 − y
Divide both sides by 2.
x = [tex]\frac{8 - y}{2}[/tex]